(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Laryngitis (Greek: larynx - "larynx") - inflammation of the mucous membranes of the larynx, usually associated with colds or infectious diseases such as measles, scarlet fever, whooping cough. The development of the disease can be caused by cooling, overheating (eating cold or hot food), breathing through the mouth, dust in the air, and straining the throat.